How to Perform a Fetotomy in Cattle: An Illustrated Guide - Myriam Jimenez; Carlos Risco; Klibs N. Galvao (EDIS)
To perform a fetotomy means to dissect (to cut apart) a dead fetus in utero. Fetotomy is applicable particularly to cows because of the size of the uterus and the opportunity to introduce instruments to the full depth of the fetus. Fetotomy is an obstetric procedure that should only be performed by a trained veterinarian or under a trained veterinarian’s supervision. This 4-page fact sheet lists the circumstances when a fetotomy can be performed to save the life of the dam, the tools needed, fetotome preparation, the sequence of cuts for anterior presentation, and final comments. Written by Myriam Jimenez, Carlos Risco, and Klibs N. Galvão, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, August 2015.